2008
DOI: 10.1590/s1516-89132008000200019
|View full text |Cite
|
Sign up to set email alerts
|

Styrene biofiltration in a trickle-bed reactor

Abstract: The biological treatment of styrene waste gas in a trickle-bed filter (TBF) was investigated. The bioreactor consisted of a two-part glass cylinder (ID 150 mm) filled with 25 mm polypropylene Pall rings serving as packing material. The bed height was 1m. Although the laboratory temperature was maintained at 22 ºC, the water temperature in the trickle-bed filter was slightly lower (about 18 ºC).The main aim of our study was to observe the effect of empty-bed residence time (EBRT) on bioreactor performance at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Inlet concentrations ranging between 50 and 1200 mg m -3 were applied and an average elimination capacity (EC) of 12 g m -3 h -1 with a maximum of 30 g m -3 h -1 was obtained. Dehghanzadeh et al (2005) used a biofilter packed with yard waste compost mixed with shredded hard plastic and observed a maximum EC of 45 g m -3 h -1 at an inlet load (IL) of 60 g m -3 h -1 and an empty bed residence time (EBRT) of 120 s. Novak et al (2008) reported a maximum EC of 11.3 g C m -3 h -1 at an IL of 18.6 g C m -3 h -1 in a BTF packed with polypropylene Pall rings working with an EBRT of 35s.…”
Section: Agency For Research On Cancer (Iarc 1987)mentioning
confidence: 99%
“…Inlet concentrations ranging between 50 and 1200 mg m -3 were applied and an average elimination capacity (EC) of 12 g m -3 h -1 with a maximum of 30 g m -3 h -1 was obtained. Dehghanzadeh et al (2005) used a biofilter packed with yard waste compost mixed with shredded hard plastic and observed a maximum EC of 45 g m -3 h -1 at an inlet load (IL) of 60 g m -3 h -1 and an empty bed residence time (EBRT) of 120 s. Novak et al (2008) reported a maximum EC of 11.3 g C m -3 h -1 at an IL of 18.6 g C m -3 h -1 in a BTF packed with polypropylene Pall rings working with an EBRT of 35s.…”
Section: Agency For Research On Cancer (Iarc 1987)mentioning
confidence: 99%
“…In recent decades, styrene removal by biofiltration has been studied at laboratory by using biofilters and biotrickling filters (Arnold et al, 1997;Dehghanzadeh et al, 2005;Novak et al, 2008;Sempere et al, 2011). Biotrickling filter (BTF), with an aqueous stream trickling through an inert packing material, provides advantages in comparison with conventional biofilter (BF) such as higher removal rates, lower energy consumption and smaller footprint requirements (Pérez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(Das et al 2008 ; Jang et al 2004 , 2005 , 2006 ; Okamoto et al 2003 ; Ryu et al 2004 ), Brevibacillus sp. (Hwang et al 2008 ), Rhodococcus pyridinovorans PYJ-1 (Jung and Park 2005 ), Exophiala jeanselmei yeast (Cox et al 1997 ), Sporothrix variecibatus fungus (Rene et al 2010 ), or mixed bacteria cultures obtained from soil or activated sludge (Arnold et al 1997 ; Babaee et al 2010 ; Djeribi et al 2005 ; El Aalam et al 1993 ; Jorio et al 2000 ; Lu et al 2001 ; Novak et al 2008 ; Pol et al 1998 ). In the research, the maximum removal rates from 91 (Cox et al 1997 ) to 635 g m −3 h −1 (Ryu et al 2004 ) were obtained depending on the used microorganisms, bed load with pollution, and empty bed resistance time.…”
Section: Introductionmentioning
confidence: 99%